Artificial reseeding improves multiple ecosystem functions in an alpine sandy meadow of the eastern Tibetan Plateau. (13th January 2023) - Tian, Lihua; Yang, Wen; Ji‐Shi, Awei; Ma, Yunhe; Zhao, Wenxue; Chen, Youjun; Zhou, Qingping; Qu, Guangpeng; Zhao, Jingxue; Wu, Gao‐Lin
Abstract: Desertification in alpine grasslands is exacerbated by rapid climate change and intensive anthropogenic activity, which will substantially threaten the structure and function of alpine grassland ecosystems. Artificial reseeding was a widely used strategy for the restoration of alpine sandy grasslands. However, it is still unclear whether reseeding restoration can improve multiple ecosystem functions of sandy meadows. To narrow these knowledge gaps, we evaluated the changes in plant communities, soil conditions, and ecosystem multifunctionality (EMF) across native meadow, sandy meadow, and restored meadow on the eastern Tibetan Plateau, and further identified the links between individual and multiple ecosystem functions. Artificial reseeding had contributed to the promotion of plant diversity, productivity, soil fertility, and soil carbon and nitrogen sequestrations. However, the recovery levels of plant diversity, productivity, and soil fertility in the restored meadow were still far lower than that in the native meadow. The results revealed that the EMF index of the restored meadow increased greatly compared with the sandy meadow, but it did not recover to that of the native meadow level. In addition, short‐term reseeding improved the aboveground EMF index more than the belowground EMF index. The EMF indexes and most individual ecosystem functions showed positive correlations with plant diversity and productivity. These findings indicated an important role of artificial reseeding in the restoration of ecosystem functions in the alpine sandy meadow, and it had critical implications for the regional ecological security and sustainable development of alpine grasslands.